Fractal: An advanced multidimensional range query lookup protocol on nested rings for distributed systems - Kargar, Saeed; Mohammad-Khanli, Leyli (Journal of network and computer applications, 2017)
One of the key issues in large-scale distributed systems such as P2P and grids is the capability of efficient multidimensional range query processing. Although several methods have recently been proposed for solving this problem on distributed systems, these methods have not been able to meet the fundamental necessity of a typical method on large-scale distributed systems, i.e., scalability. This paper presents Fractal, a fully decentralized and highly scalable multidimensional range query lookup protocol for distributed systems. In this work, to organize the available nodes in the system, an n-dimensional space called Key Space is utilized. The available nodes on the nested Fractal rings maintain information about only O(logN) other nodes, and the Fractal lookup protocol discovers the destination node through these nested rings with a logarithmic cost. Because of its flexibility, Fractal allows the system to create a concept called Layering, which minimizes the probability of the wide-area message transfers (WAMTs) during the lookup process. Using several criteria, Fractal is compared with several successful methods that have recently been presented. Simulation results show the efficiency and performance of Fractal in networks of different sizes. •This paper presents Fractal, a lookup protocol for distributed systems such as loT.•Fractal has succeeded to achieve the logarithmic cost without sacrificing efficiency.•The concept of layering can be added to the system as a solution to the WAMT problem.•Fractal adds the economic state to the lookup methods for the first time.•Fractal can be a good alternative for use in real-world distributed systems.